This study investigates the cost of increasing dietary diversity for livestock producers who minimize the cost of supplying nutrients to animals. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
We illustrate illustrate the technical aspects of the new livestock module of the IMPACT model, while also presenting initial results across different geographies.